Improved Detection of Citrus psorosis virus and Coat Protein‐Derived Transgenes in Citrus Plants: Comparison Between RT‐qPCR and TAS‐ELISA - de Francesco, Agustina (2015)
Citrus is one of the most economically important fruit crops in the world. Citrus psorosis is a serious disease affecting mainly oranges and mandarins in Argentina and Uruguay. The causal agent is Citrus psorosis virus (CPsV), an ophiovirus with a tripartite ssRNA genome of negative polarity. The coat protein (CP), the most abundant viral protein in infected plants, has been used to detect CPsV by TAS‐ELISA, but only biological indexing, requiring 1 year, is the current and validated technique for diagnosis of citrus psorosis. In this study, a SYBR Green RT‐qPCR protocol was developed, with primers designed to the most conserved region of the cp gene. We tested their specificity and sensitivity in comparison with TAS‐ELISA. This RT‐qPCR was applied successfully to field samples from Argentina, to a variety of isolates from different countries maintained in the greenhouse, to young seedlings and old trees from a psorosis natural transmission plot, and to transgenic citrus expressing the cp gene of CPsV or a fragment thereof. This method allowed accurate quantification of viral titer and cp gene expression in transgenic plants, which could not be detected previously. The sensitivity and reliability of quantitative CPsV detection were improved with greater speed using commercial reagents, and the sensitivity was three orders of magnitude higher than that of TAS‐ELISA. All these data encourage its validation.